Deciphering the Formulation Secret Underlying Chinese Huo-Clearing Herbal Drink - Wang, Jianan; Zhou, Bo; Hu, Xiangdong; Dong, Shuang; Hong, Ming; Wang, Jun; Chen, Jian; Zhang, Jiuliang; Zhang, Qiyun; Li, Xiaohua; Shikov, Alexander N.; Hu, Sheng; et al. (Frontiers in Pharmacology, 2021)
Herbal teas or herbal drinks are traditional beverages that are prevalent in many cultures around the world. In Traditional Chinese Medicine, an herbal drink infused with different types of medicinal plants is believed to reduce the ‘Shang Huo’, or excessive body heat, a status of sub-optimal health. Although it is widely accepted and has a very large market, the underlying science for herbal drinks remains elusive. By studying a group of herbs for drinks, including ‘Gan’ (Glycyrrhiza uralensis Fisch. Ex DC.), ‘Ju’ (Dendranthema morifolium (Ramat.) Tzvelev), ‘Bu’ (Microcos paniculata L.), ‘Jin’ (Lonicera japonica Thunb.), ‘Xia’ (Prunella vulgaris L.), and ‘Ji’ (Plumeria rubra L.), the long-term jargon is connected with the inflammation of modern immunology through a few pro-inflammatory markers. In vitro studies have indicated that cellular inflammation is lowered by Ju and Jin either individually or synergistically with Gan. Among all herbs, only Gan detoxicated cellular toxicity of Bu in a dose dependent manner. The synergistic formulation of Ju and Gan, or Jin and Gan, in a reduction of Shang Huo, was tested in vivo. Both combinations exhibited a lower percentage of neutrophils, monocytes, and CD4+/CD8+ ratio in the blood, as well as inflammatory cytokines. Furthermore, body weight in the combinatory groups was more stable than treatments using single herbs. The combination of old traditional oriental methods with Western science logistics, has resulted in the formulation of different herbs into one concoction for the use of detoxification and synergism.